Victim-Blaming & Sexual Aggression Myths: Assessing the Impact on Bystander Behavior Among College Students - (:unkn) unknown (My University, 2025)
Background: Sexual violence is a significant issue in the United States, particularly on college campuses, where the rates remain alarmingly high. Despite extensive research conducted in this area, sexual violence continues to be a persistent problem. One major challenge in addressing this issue might be the reliance on outdated tools and concepts that no longer accurately reflect the current social climate. This challenge not only pertain to the prevalence of sexual violence but also affect the experiences and safety of survivors. This situation raises critical questions about the effectiveness of current bystander training programs on college campuses. Three theoretical frameworks are utilized—bystander theory, sexual aggression myths, and real rape—to thoroughly examine bystander training and its impact on sexual aggression myths, victim blaming, and bystander behaviors.Methods: This dissertation effectively addresses significant gaps in the existing literature and comprises three impactful manuscripts (Chapters Two, Three, and Four). The first manuscript delivered a comprehensive systematic review and meta-analysis of studies published from 2015 to 2024, examining the effects of bystander training on negative perceptions (i.e., rape myths, sexism) and prosocial behavior (i.e., bystander efficacy, intentions to help) using five electronic databases. The second study employed original survey data collected from 2,884 participants across four universities within the Universities of Wisconsin. The study randomly assigned participants to one of eight conditions, where they read a sexual assault scenario that was manipulated based on the condition to assess victim-blaming and its relationship to bystander behavior. The third study also utilized the original survey data to introduce a revised version of sexual aggression myths, denoting the Gender-Inclusive Acceptance of Modern Myths on Sexual Aggression (GIAMMSA). This manuscript rigorously explored the differences between the GIAMMSA and the Gender-Inclusive Rape Myths Scale (GIIRMAS) and how the myths might impact prosocial bystander behavior. Results: The first study highlighted a significant lack of research. Only eleven articles examined the impact of bystander training on one of four variables: rape myths, sexism, bystander efficacy, and intentions to help, using randomized control trials. None of the articles utilized the new sexual aggression myths construct, and only six addressed rape myth acceptance. Additionally, none of the studies included non-binary populations, and only four provided information about cisgender relationships. This initial study uncovered substantial gaps in the existing research, which the following two studies aimed to address. The second study revealed differences in victim-blaming based on vignette variation on the sex of both the survivor and the perpetrator. Specifically, when the survivor was male, survivors received significantly more blame for the assault. Self-blame was lower when the survivor was female, and the perpetrator was male. Victim-blame was significantly higher when the sexual assault was “stopped” as opposed to when it was “completed.” Additionally, survivors of sexual assault reported higher levels of self-blame, which was associated with worse mental health. Concerningly, higher levels of victim-blame correlated with an increase in prosocial bystander behaviors and bystander training did not moderate the relationship between prosocial bystander behaviors and victim-blame. The third study demonstrated that the revised version of the sexual aggression myths scale, known as GIAMMSA, is a robust and reliable unidimensional construct, achieving an alpha coefficient of .89. The GIAMMSA yielded significantly higher scores compared to the GIIRMAS. Notably, the GIIRMAS model struggled to converge based on the five proposed factors, while principal factor analysis revealed weak loadings. Multiple regression analyses did not find a significant relationship between sexual aggression myths and prosocial bystander behavior; therefore, the relationship remains unclear. Implications: Current bystander trainings might not be doing enough to combat sexual violence and unknowingly be increasing victim-blaming, and individuals who did not take the training had higher prosocial bystander behaviors. Several areas for future research exist, including determining how sexual aggression myths influence the perpetration of sexual violence and sexist mentalities, exploring how victim-blaming differs across genders and non-binary populations, identifying why trainings might increase negative perceptions towards survivors, and conducting additional research examining all types of sexual violence, not simply male-on-female violence. As such, it is suggested that the current training be updated to a required one-semester course for incoming students, with yearly refresher training, in which more information is provided about consent, stereotypes related to sexual violence, self-defense, promoting anti-victim-blaming attitudes, and offering specific guidance on how to support friends who have experienced sexual assault.
Keywords: Criminology; Bystander Behavior; College Students; Rape Myths; Sexual Aggression Myths; Sexual Violence; Victim Blaming